THE ESSENCE AND FEATURES OF SOCIAL PARTNERSHIP BETWEEN LOCALGOVERNMENTS, PUBLIC ORGANIZATIONS AND BUSINESS REPRESENTATIVES - TERENYAK, Liliya; KUZEMKO, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the urgent problem of interaction between local self-government, public organizations and business as a form of social partnership in achieving a common goal: social well-being of the local community.In our opinion, the optimal solution to social problems and the basis for successful economic modernization of the country will be the creation of an effective social partnership system, which will be a decisive factor for mobilizing local and regional resources. It is more effective to start building this system from the community territory, given the greatest commonality of interests of representatives of the three sectors at the local level. Intersectoral partnership is a constructive interaction between organizations of two or three sectors to solve social problems, benefiting each of the parties individually and the population of the territory where it is implemented, in particular. The development of intersectoral partnerships in Ukraine is a complex and controversial process, complicated by the lack of information about each other, the absence of a well-developed legal framework, unclear financial mechanisms, and the low level of trust between the participants and the local community. The prerequisites for the formation of such a system are, in particular, spontaneously formed social networks between participants, awareness of the need for joint action to reform the social sector, and practical experience in implementing trilateral social projects. The most viable models of social partnership at the moment are: community foundations, youth initiative banks, public councils, and social project fairs. At the moment, these models have not developed into a single system of social partnership. However, the process of social partnership development seems to us similar to the provisions of synergetics about integration and the desire of open nonlinear systems to become a single complex evolutionary whole.